THE ACTIVITIES OF THE CONSTITUTIONAL COURT OF UKRAINE IN THE CONTEXT OF PROTECTING THE RIGHTS AND FREEDOMS OF MAN AND CITIZEN IN UKRAINE - Задорожня, Г. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
The article examines the activities of the Constitutional Court of Ukraine in the context of protecting human rights and freedoms in Ukraine.